KAJIAN PENGARUH VARIASI JUMLAH LAPISAN TRANSPARAN TiO2 TERHADAP PERFORMA KERJA SEL SURYA YANG DISENSITISASI DENGAN DYE (DSSC) - Ida Usman; Purwo Adi Setyo; Waode Sukmawati Arsyad (Jurnal Aplikasi Fisika, 2017)
A study of the effect of variations on the number of transparent TiO2 layers on dye-sensitized dye (DSSC) solar cell performance has been conducted. This study aims to make DSSC solar cell with transparent amount of transparent TiO2 transparent layer and characterize its working function by measuring the photovoltaic characteristics. From the results of the research, the Jsc value obtained increases with the increase in the number of layers for the case of cells A and B cells, this is probably related to the increasing number of dye that binds to TiO2 with increasing cell thickness, thus increasing the amount of light absorbed by dye . However, when the thickness of the TiO2 layer is added (cells C and D) the Jsc value actually decreases. A DSSC A cell with a layer of transparent TiO2 layer of 1 layer shows the largest open circuit voltage value of 0.7V, while DSSC B cells show the highest current density value of 2.07mA / cm2, and the highest fill factor (FF) is indicated by Sample D. The results of this study there are many factors that limit the effesiensi DSSC solar cellsKeywords: DSSC, TiO2 Transparent, Number of Layers, Performance